2007
DOI: 10.1021/ol7024058
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Diels−Alder/Tsuji Allylation Assembly of the Functionalized trans-Decalin of Salvinorin A

Abstract: An enantioselective synthesis of the highly functionalized trans-decalin core (2) of salvinorin A is described. The tetraene 4 was synthesized in six steps from a known L-(+)-tartaric acid derivative. Three contiguous stereocenters, two of them quaternary, on the trans-decalin were established asymmetrically by an intramolecular Diels-Alder/Tsuji allylation sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 26 publications
(26 reference statements)
1
23
0
Order By: Relevance
“…A remarkable arrangement is observed in the first substituent (O22•••C28), where disordered final CCH 2 groups are placed almost perpendicular, reflecting a high degree of free rotation about σ bonds in these substituents. This behavior, resulting in a variety of stable conformations for the allylcarbonate functional groups, has been also observed in related structures (Michelet et al, 2003;Burns & Forsyth, 2008;Flores Ahuactzin et al, 2009). In (I), the observed disorder may be related to the rather low melting point of this material, 318 K (45° C).…”
Section: Data Collectionsupporting
confidence: 56%
See 1 more Smart Citation
“…A remarkable arrangement is observed in the first substituent (O22•••C28), where disordered final CCH 2 groups are placed almost perpendicular, reflecting a high degree of free rotation about σ bonds in these substituents. This behavior, resulting in a variety of stable conformations for the allylcarbonate functional groups, has been also observed in related structures (Michelet et al, 2003;Burns & Forsyth, 2008;Flores Ahuactzin et al, 2009). In (I), the observed disorder may be related to the rather low melting point of this material, 318 K (45° C).…”
Section: Data Collectionsupporting
confidence: 56%
“…For the crystal structure of 4-(hexyloxy)aniline, used as a starting material, see: Herrera et al (2005). For the crystal structures of molecules with allycarbonate functionality, see: Michelet et al (2003); Burns & Forsyth (2008); Flores Ahuactzin et al (2009). For applications of the above molecules as polymerizable monomers, see: Herrera (2006).…”
Section: Related Literaturementioning
confidence: 99%
“…All structural derivatization studies reported to date have involved systematic modification of salvinorin A extracted directly from the leaves of S. divinorum. Several total synthesis efforts have been reported (Lingham et al, 2006;Scheerer et al, 2007;Burns and Forsyth, 2008;Nozawa et al, 2008;Bergman et al, 2009;Hagiwara et al, 2009); however, their time and resource investment, compared with the relative ease in isolation from natural sources, render their application thus far suboptimal for use in SAR development. Binding affinities and functional activities of analogs at MOP, DOP, and KOP receptors are described in Table 1.…”
Section: A Structure-activity Relationships Of Analogsmentioning
confidence: 99%
“…Despite their advantages, these alkylation reactions were rarely utilized during the twenty years between 1983 and the time we began research in 2003. [23,24] Our analysis of Tsujis alkylation reaction showed it to be an ideal candidate for asymmetric catalysis. These highyielding alkylation methods are a clear case of ligand-accelerated catalysis, occurring only in the presence of phosphine ligands.…”
Section: Introductionmentioning
confidence: 98%